Study of UV bright sources in globular cluster NGC 4590 using Ultraviolet Imaging Telescope (UVIT) observations. Issue 4 (11th February 2022) - Kumar, Ranjan; Pradhan, Ananta C; Parthasarathy, M; Piridi, Sonika; Cassisi, Santi; Ojha, Devendra K; Mohapatra, Abhisek; Murthy, Jayant
ABSTRACT: We have studied ultraviolet (UV) bright sources in the Galactic globular cluster (GGC) NGC 4590 using Ultraviolet Imaging Telescope onboard the AstroSat satellite. Using UV-optical colour–magnitude diagrams (CMDs), we have identified and characterized the sources of different evolutionary stages i.e. blue horizontal branch stars (BHBs), extremely blue horizontal branch stars (EHBs), blue straggler stars (BSs), variable stars, etc. We estimated effective temperature ( T eff ), gravity (log (g)), luminosity ( L bol ), and hence the radius (R) of these hot stars by fitting spectral energy distribution with the help of stellar atmosphere models. Two new far-UV bright cluster member stars situated near the core of the cluster have been detected; one of them is an EHB star and the other one is either in its post-blue hook evolutionary phase or in white dwarf phase. The evolutionary status of all the hot stars, identified in the cluster, has been investigated by using various evolutionary models. We find the massive and younger BSs are concentrated at the centre of the cluster whereas the older and less massive BSs are distributed throughout the cluster. The BSs normalized radial distribution seems to be bi-modal with a minimum located at rmin = 4.3 r c . We calculated A + parameter of the cluster which is obtained using cumulative normalized radial distribution of horizontal branch stars (HBs) and BSs. We measured this value up to half-mass radius of the cluster to be +0.13, which indicates that NGC 4590 is one of the youngest clusters among dynamically intermediate age GGCs with a dynamical age of 0.423 ± 0.096 Gyr.